我国现阶段财政支出与财政收入政策间的结构特征分析 - 刘伟 (财贸经济, 2012)
本文考察了现阶段我国财政收入与财政支出政策相互间结构关系特征.我国长期以来采取扩张性的财政支出政策,同时财政收入政策相对从紧.财政收入绝对增长的同时,占GDP比重持续上升.在采取了一系列减税政策的同时,企业赋税压力并未减弱.地方政府普遍财政支出大于一般预算收入,中央转移支付力度不断加大,地方政府本身平衡预算的能力和责任在制度上缺乏可能等等,都构成我国财政政策效应的特点,都需要深入讨论.The?paper?analyzes?the?characteristics?of?structural?relationship?between?fiscal?revenue?and?expenditure?policies?of?China.?China?has?taken?an?expansionary?fiscal?expenditure?policy?for?a?long?time?while?fiscal?revenue?policy?was?relatively?tight.?Not?only?has?absolute?fiscal?revenue?increased,?but?also?the?ratio?of?total?fiscal?revenue?in?GDP?risen?continually.?Tax?burdens?of?most?enterprises?have?not?been?reduced?actually?after?a?series?of?measures?of?tax?reduction?were?applied.?The?characteristics?of?fiscal?policy?effects?of?China?which?should?be?investigated?further?include.?(1)?fiscal?expenditures?of?local?governments?in?province?level?generally?were?more?than?their?fiscal?revenues,?(2)?the?degree?of?the?transfer?payments?from?central?government?to?local?governments?enhanced?continually,?(3)?the?ability?and?responsibility?of?local?governments?to?balance?their?own?fiscal?budgets?generally?could?not?be?realized?in?current?institutional?arrangement.
Keywords: Fiscal Revenue Policy; Fiscal Revenues and Expenditures of Central Government and Local Governments; Transfer Payments; 财政支出政策; 财政收入政策; 转移支付; 中央财政与地方财政; Fiscal Expenditure Policy